FORMULASI DAN UJI ANTIBAKTERI EKSTRAK BIJI KETUMBAR (Coriandrum sativum L.) PADA SEDIAAN SPRAY GEL ANTIJERAWAT DENGAN VARIASI CARBOPOL 940 - Muhammad Zielal Askari; Muhammad Nurul Fadel; Bintari Tri Sukoharjanti (Nusantara Hasana Journal, 2025)
Acne is a skin problem or infection that generally appears on the face, neck, chest, and back. Acne is caused by the bacteria Propionibacterium acnes. Acne treatments that are often used are topical medications containing synthetic antibiotics. However, the use of these drugs can cause adverse resistance. Another alternative for acne therapy is using natural ingredients. This study aims to determine the antibacterial activity of coriander seed extract in a spray gel preparation. Flavonoid, terpenoid, saponin and tannin compounds contained in seeds This study is an experimental laboratory study using the disc diffusion method with 5 treatments, namely coriander seed extract with a concentration of carbopol F1 0.1%, F2 0.2%, F3 0.3%, a positive control spray gel brand "X" and a negative control only base without extract. The process of making coriander seed extract is carried out through the maceration method for 3x24 hours with 70% ethanol solvent. The filtrate obtained is then evaporated using a water bath to become a thick extract and continued for making spray gel preparations and antibacterial testing. The results of the research on the spray gel formulation from coriander seed extract showed the organoleptic physical characteristics of F1, F2, F3 were yellowish brown, liquid, and had a distinctive coriander odor. The pH test was 6.46; 6.32; 6.04, the viscosity test was 93.43 cP; 81.10 cP; 78.67 cP, the adhesiveness test of all formulas was stated not to drip for 10 seconds, and the spreadability was 6.01 cm; 5.48 cm; 4.42 cm. In the antibacterial test of the spray gel preparation, the inhibition zone value was obtained, namely F1 5.97 mm, F2 6.05 mm, F3 6.08 mm, and the positive control 10.10 mm. Based on the research of the three formulations, the most optimal spray gel preparation was F2 because it met the requirements of the physical test and antibacterial test.